PHOSPHORUS FORMS AND DISTRIBUTION IN TWO DIFFERENT PARENT MATERIALS IN JOS PLATEAU STATE - Dughuryil, M. K.; Hassan, A. M.; Voncir, N.; Kosshak, A. S. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study investigates the distribution of phosphorus (P) forms in soils derived from basaltic (BPM) and granitic (GPM) parent materials in Jos, Plateau State. One profile was dug at each identified parent material. Routine field and laboratory analysis were carried out. Results demonstrate that parent material influences both the concentration and variability of P forms. Soils developed from basalt consistently exhibited higher mean contents of aluminum-bound P (Al-P: 104.56 mg/kg), calcium-bound P (Ca-P: 51.89 mg/kg), reductant-soluble P (Red-P: 118.60 mg/kg), occluded P (Occ-P: 70.89 mg/kg), available P (Av-P: 7.36 mg/kg), and total P (TP: 838.26 mg/kg) compared to their granite-derived counterparts. The distribution of these P forms down the soil profile was predominantly irregular for most forms, though Occ-P showed a consistent increase with depth in both soil types. Variability, measured by the coefficient of variation (CV), was generally low to moderate (<30%) for most P forms. However, GPM soils displayed greater variability in Al-P distribution, while Ca-P in GPM was highly variable (CV 53.94%). The overall abundance of P forms followed the order Fe-P > O-P > Red-P > Al-P > Occ-P > Ca-P > Av-P for BPM and O-P > Fe-P > Red-P > Al-P > Ca-P > Occ-P > Av-P for GPM. The higher P contents observed in this study compared to some previous works are potentially attributable to continuous fertilizer usage in the study area. A key agronomic finding is that despite these inputs, available phosphorus levels fell below the 10 mg/kg critical threshold for optimal crop production, indicating potential phosphorus deficiency.